Revision of the genera Interrhodeus, Pennarhodeus and Poropodalius (Acari: Rhodacaridae) - Castilho, Raphael C.; de Moraes, Gilberto J.; Halliday, Bruce (Zootaxa, 2012)
The genera Interrhodeus Karg, Pennarhodeus Karg and Poropodalius Karg are redescribed on the basis of one species ofInterrhodeus, four species of Pennarhodeus and five species of Poropodalius, including the type species of each genus.All species are redescribed on the basis of the type specimens, and keys for the separation of the species of the latter twogenera are provided. Re-examination of these species shows that these three genera are correctly placed in the family Rhodacaridae.